Studies of BDOC and bacterial dynamics in the drinking water distribution system of the Northern Parisian suburbs - Servais, P.; Billen, G.; Laurent, P.; Levi, Y.; Randon, G. (Revue des sciences de l'eau / Journal of Water Science)

(untitled) (Université du Québec - INRS-Eau, Terre et Environnement (INRS-ETE), 1992)
The deterioration of water quality in distribution systems due to bacterial regrowth is, at the present time, a major concern of drinking water producers. In this context, a good knowledge of the factors controlling bacterial development is required; the aim of the present study is to understand the rote of biodegradable dissolved organic carbon (BDOC) in the bacterial dynamics of the distribution system.This paper discusses the results obtained in a study carried out in order to assess the dynamics of biodegradable dissolved organic carbon and suspended bacteria in the water distribution system of the Northern Parisian suburbs lad by the Méry-sur-Oise treatment plant.The results show clearly that a significant decrease in BDOC occurs within the smallest pipes, when the BDOC level in the finished water is higher than about 0.20 mgC.L-1. However, no decrease in BDOC is observed when the BDOC in the finished water is lower than 0.16 mgC.L-1. The bacterial abundance in the distribution system is primarily linked to the absence of free chicane. Temperature and BDOC concentration in the finished water are also major controlling factors of bacterial numbers. Bacterial growth rates are in the range 0.005 to 0.1 h-1 in the absence of free chlorine, the highest of these values are in the same range as the growth rates measured for bacteria in natural aquatic ecosystems. Fixed biomass to the inner pipes surface are in the range 0.25 to 0.65 µgC.cm-2 and the average growth rate of fixed bacteria seems to be roughly in the same order of magnitude as the average growth rate of the suspended bacteria.A model of the dynamics of BDOC and bacteria in distribution network, incorporating the knowledge gained from this and previous studies concerning the control of bacterial activity by dissolved organic matter, is presented. It involves a mathematical representation of the kinetics of bacterial adsorption-desorption processes, bacterial attachment, bacterial utilization of biodegradable dissolved organic matter and impact of chlorine on free and fixed bacteria. It allows simulation of the impact of reducing the BDOC in the finished water on processes associated with bacterial regrowth in the distribution network..